Thermal performance of in-between shading systems in multilayer glazing units: Hot-box measurements and numerical simulations. (September 2015) - Grynning, Steinar; Misiopecki, Cezary; Uvsløkk, Sivert; Time, Berit; Gustavsen, Arild
Shading systems are widely used, also in Nordic climates, in conjunction with glazed facade in office buildings. The primary functions of the solar shading devices are to control solar gains leading to cooling needs during operational hours and reduction of discomfort caused by glare. A secondary property of shading devices incorporated in glazing units is that they can be utilized as an additional layer in the glazing unit when the shading device is deployed. This can improve the thermal transmittance value (U-value) of the windows. It can be deployed during night-time or in periods when a blocked view does not have any consequences for the users of the building. This article presents hot-box measurements of thermal transmittance values (U-values) performed for three insulated glazing units with integrated in-between pane shading systems. The shading devices are venetian-type blinds with horizontal aluminum slats. The windows with double- and triple-pane glazing units have motorized blinds. The window with a 4-pane glazing has a manually operated blind placed in an external coupled cavity. The measurements are compared to numerical simulations using the WINDOW and THERM simulation tools. The results showed that only minor reductions of U-values of the glazing units were obtained as function of shading system operation. It was, however, found that the introduction of shading devices in the window cavities will increase the total U-value of the window due to thermal bridging effects caused by shading device motor and the aluminium slats of the blinds. coupled cavity.